PROMES SERIBU ATM Mewujudkan High Skill dalam Pembuatan Dokumen - Jaenali Jaenali (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2021)
The skills that must be possesed by students of the Automation and Governance (OAG) competency are making document with predetermined standards. OAG students have not been able to meet the time standard and the number of errors in making documents. The author combines a ten-finger typing system with a blind typing system using the Typing Master application. PROMES THOUSAND ATM is an acronym for Ten Finger Blind System Typing Program Using Typing Master Application. This program has been implemented since the 2016/2017 academic year at SMK Negeri 2 Tegal. Through this learning strategy, students can create documents according to standards. It is proven by the increase in learning outcomes for Office Technology subjects, PKL scores and UKK OTKP scores. With an average learning completeness of 91.09%, an increase in the value of street vendors by 90.59% and the achievement of the UKK score with an average of 91 on the task of making documents.